2022
DOI: 10.1007/s40429-022-00411-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Considerations of Ultra-processed Food Addiction Across Weight Classes: an Eating Disorder Treatment and Care Perspective

Abstract: Purpose of Review To examine the prevalence rates of ultra-processed food addiction across different weight classes and offer guidelines for diagnosis and treatment. Clinicians are provided with practical considerations in the assessment of ultra-processed food addiction beyond the use of validated instruments. Recent Findings The weighted mean prevalence of ultra-processed food addiction is approximately 20% worldwide and varies widely based on the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 144 publications
0
19
0
Order By: Relevance
“…Another study found 5.5% of normal weight and 15% of underweight people have food addiction ( 41 ). However, people often pursue treatment in the hope of achieving this goal, which is one reason that many ED professionals criticize this field ( 7 ). Weight loss was significant across the study sites at this stage of follow-up despite it not being a focus of the programs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another study found 5.5% of normal weight and 15% of underweight people have food addiction ( 41 ). However, people often pursue treatment in the hope of achieving this goal, which is one reason that many ED professionals criticize this field ( 7 ). Weight loss was significant across the study sites at this stage of follow-up despite it not being a focus of the programs.…”
Section: Discussionmentioning
confidence: 99%
“…There is also ongoing discussion amongst clinicians as to how to refer to this disorder. For the purposes of this paper, we will use the term food addiction to refer to dependency behaviors relating to sugar and processed foods, although it is increasingly being referred to as ultra-processed food addiction ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations